Semilocal analysis of equations with smooth operators. (1981) - Miel, George J.
Abstract : Recent work on semilocal analysis of nonlinear operator equations is informally reviewed. A refined version of the Kantorovich theorem for Newton's method, with new error bounds, is presented. Related topics are briefly surveyed.